Green synthesis of silver nanoparticles from vegetable waste of pea Pisum sativum and bottle gourd Lagenaria siceraria: Characterization and antibacterial properties - Deepa,; Ameen, Fuad; Amirul Islam, M.; Dhanker, Raunak (Frontiers in Environmental Science, 2022)
A huge amount of food waste is being generated every day globally. Usually, India generates ~350 million tonnes of food waste every year. Therefore, there is an urgent need to initiate research focusing on the management and hygienic methods of reuse of food waste together with advanced user-friendly methods of converting it into some useful products. Thereby generating wealth from food waste. A promising approach seems to be to biosynthesize silver nanoparticles (AgNPs) from such unutilized food. An alternative clean technology does not rely on the use of toxic chemicals and solvents. It is commonly allied with traditional nanoparticle synthesis processes. In present work, peel of two vegetables pea (Pisum sativum) and bottle gourd (Lagenaria siceraria) were used to generate AgNPs. AgNPs were obtained by dissolving 1.5 ml peel extract of each vegetable in 50 ml of silver nitrate (AgNO3) and incubating for 24 hour at room temperature. For the confirmation of AgNPs production UV-visible spectroscopy was used. Field Emission Scanning Electron Microscopy (FESEM) and X-ray Diffraction (XRD), Attenuated total reflection-infrared spectroscopy (ATR-IR Analysis) were used to characterize them. Further, AgNPs in different concentrations were used to test antibacterial activity against bacteria Escherichia coli through the Disc diffusion Method. Thus, our research indicates that AgNPs can be a safe and environmentally beneficial production technology from unutilized vegetable wastes that may play an important role in the management of food waste in future and has antibacterial potential to preserve vegetables from bacterial contamination.